Sosialisasi Riset Program Kampus Merdeka Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Kendari - Al Kahfi; Rheza Yudha Pradana; Wilin Apriani Harjarombe; Windy Eka Pratama; Amin Mubarak; Muh Sahir; Muh Tinokabarak B; Citra Prasiska Puspita Tohamba (BADAN PENERBIT STIEPARI PRESS, 2024)
The Independent Campus Program is an educational breakthrough in Indonesia that gives students the freedom to manage the course of education. This concept emphasizes the principle of academic freedom, where students have full control in designing the curriculum, choosing courses, and determining the course of learning. The main goal of Kampus Merdeka is to produce graduates who not only have academic knowledge, but also practical skills that are relevant to the needs of industry and society. The program invites students to be active in extracurricular activities, internships, and collaborative projects. In addition, Kampus Merdeka provides space for the development of creativity, innovation, and entrepreneurial spirit. Students are empowered to pursue their interests and talents, creating a more meaningful learning experience. The implementation of Kampus Merdeka has created a positive impact in shaping students who are more independent, adaptive, and ready to face the world of work. The community's response to this program is quite positive, but the challenges of implementation and adjustment are still the focus of discussion. Thus, Kampus Merdeka is a step towards transforming education that is more dynamic and relevant to the demands of the times.